1983
DOI: 10.3758/bf03334710
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, permanent, loss of memory for absolute intensity of taste and smell

Abstract: Memory formation for the absolute intensity of taste and smell was investigated in a series of experiments. In Experiment I, 336 subjects tasted 10 ml of 15% sucrose and were asked to remember the strength of the solution. They were retested with 5%, 10%, 15%, or 20% sucrose, at one of four delay intervals (1, 5, or 15 min, or 72 h). They compared the second stimulus with the first stimulus and reported whether the second was "less sweet," "the same," or "sweeter." Subjects reliably reported that 5% sucrose wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 4 publications
4
25
0
Order By: Relevance
“…In an incidental learning experiment with elderly people, the participants showed a clear tendency to perceive several attributes of soup targets as less intense than they remembered them. In contrast, young people showed a slight tendency to underestimate the remembered target just like the participants in the experiments of Kö ster et al (2004) and of Barker and Weaver (1983) who interpreted this phenomenon as the fading of a memory trace. Obviously, shifts in memory may occur, but their occurrence and direction depend on a number of factors such as the food-attribute combination and perhaps on such subject-related factors as age.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In an incidental learning experiment with elderly people, the participants showed a clear tendency to perceive several attributes of soup targets as less intense than they remembered them. In contrast, young people showed a slight tendency to underestimate the remembered target just like the participants in the experiments of Kö ster et al (2004) and of Barker and Weaver (1983) who interpreted this phenomenon as the fading of a memory trace. Obviously, shifts in memory may occur, but their occurrence and direction depend on a number of factors such as the food-attribute combination and perhaps on such subject-related factors as age.…”
Section: Discussionmentioning
confidence: 63%
“…Shifts in memory opposite to the one found here have also been reported in taste memory research. Barker and Weaver (1983) and Kö ster et al (2004) found that in their experiments the participants underestimated the sweetness intensity of their remembered targets. Nevertheless, a shift in the same direction as in the present experiment was found by Møller et al (2007).…”
Section: Discussionmentioning
confidence: 95%
“…Taste studies requiring judges to match taste intensities of previously tasted stimuli, by mixing strong and weak components, indicated a tendency to overestimate the intensity of stimuli tasted immediately beforehand (Theunissen, Tuorila, & Ahlströ m, 1993;Tuorila, Theunissen, & Ahlströ m, 1996;. For taste and odor stimuli, Barker and Weaver (1983) required judges to state whether a stimulus was greater, lesser or equal in intensity to stimuli tasted 1 min before; they found a tendency to underestimate the intensity of the previous stimulus. Either way, memory of stimulus intensities was prone to error.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was considered to be immune to interference from backward counting tasks, to lack a short-term memory store (Engen, Kuisma, & Eimas, 1973), and to have a unique flat forgetting curve, that is, poor initial scores and high retention over time (Engen & Ross, 1973). Recent findings, however, indicate that distractor odors interpolated between odor learning and testing decrease memory performance (Walk & Johns, 1984), a short-term store for odor intensity seems to exist (Barker & Weaver, 1983), and the forgetting curves of both odors and ambiguous, undefined shapes are similar (Lawless, 1978). For a recent review of odor memory, see Schab (1991).…”
Section: Perceptionmentioning
confidence: 99%